Professional burnout as an origin and development factor for hypochondriacular personality disorders - Viznyuk, Iniessa (Professional Pedagogics, 2018)
The article focuses on the essence of hypochondria disorders origin and development mechanisms while an individual’s professional burnout and their basic psycho diagnostic approaches. The disorder symptomatic features list under control and experimental groups’ differential similarities and differences conditions is indicated. Common scientific methods are used for studying diverse sources and literature following by recreating real facts of the studied problem taking into account native scientists’ scientific works results. The hypochondria nosologies definition’s etiology and development of the testing group in their professional activity is analysed. The attention is brought to their vital values and priorities for determining future priorities with pathogenetic suggestion of complaints on their own health dysfunction.The credibility of the topic was provided by unbiased, non-populist conclusions, taking into account previous researchers’ views and reliable and proven information from selected sources. At the same time, we did not give a wide berth to critical judgments and evaluations for realistic representing a number of psychosomatic problems in hypochondriac disorders genesis.The complex approach is used for representing main hypochondria psycho diagnostics and treatment ways as an individual’s psychological burnout mechanism. The diagnostics basic principles context complexity is characterized by methods multimodality for collecting information on disease etiology. In its context, account is taken to the ability of integrating the information obtained by different methods. Inter alia, the particular focus is put on detecting the range of development determinant for the following nosogenic phenomena: biological (includes biochemical, neurophysiologic, psycho- physiological spheres) ...
Keywords: psychological burnout; psycho diagnostics; hypochondria disorders; psychosomatic disorders; psycho diagnostic principles